The impact of early musical training on striatal functional connectivity - van Vugt, F.T.; Hartmann, K.; Altenmüller, E.; Mohammadi, B.; Margulies, D.S. (NeuroImage (Orlando, Fla.), 2021)
•Early childhood piano training has a long-term impact on functional connectivity between ventral striatal and sensorimotor cortical regions not observed for training later in life.•Early trained musicians showed greater expertise as measured using temporal precision in musical scale playing.•Functional connectivity between striatum and sensorimotor cortex correlated with musical expertise measurements.•Musical training, regardless of when it is initiated, has profound effects on brain structure and function. Evidence from language, visual and sensorimotor learning suggests that training early in life is more effective. The present work explores the hypothesis that learning during sensitive periods involves distinct brain networks in addition to those involved when learning later in life. Expert pianists were tested who started their musical training early (<7 years of age; n = 21) or late (n = 15), but were matched for total lifetime practice. Motor timing expertise was assessed using a musical scale playing task. Brain activity at rest was measured using fMRI and compared with a control group of nonmusicians (n = 17). Functional connectivity from seeds in the striatum revealed a striatal-cortical-sensorimotor network that was observed only in the early-onset group. In this network, higher connectivity correlated with greater motor timing expertise, which resulted from early/late group differences in motor timing expertise. By contrast, networks that differentiated musicians and nonmusicians, namely a striatal-occipital-frontal-cerebellar network in which connectivity was higher in musicians, tended to not show differences between early and late musicians and not be correlated with motor timing expertise. These results parcel musical sensorimotor neuroplasticity into a set of musicianship-related networks and a distinct set of predominantly early-onset networks. The findings lend support to the possibility that we can learn skills more easily early in development because during sensitive periods we recruit distinct brain networks that are no longer implicated in learning later in life.